(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A simple, sensitive and rapid spectrophotometric methods were developed and validated for the determination of two antihypertensive drugs namely, carvedilol and nebivolol hydrochloride in pure form and pharmaceutical formulations. Method (I) is based on the formation of a binary complex between the studied drugs and eosin Y in presence of tween 80 at (pH 3.0).The formed complex exhibited maximum absorption at 545 nm for carvedilol and 543 nm for nebivolol. The concentration plots were rectilinear over concentration range of 0.5-5 and 1-7 µg/mL with lower detection limits of 0.09 and 0.11µg/mL and lower quantitation limits of 0.28 and 0 .34 µg/mL for carvedilol and nebivolol respectively. Method (II) is based on the reaction of studied drugs through their secondary amino groups with 2, 4-dinitrofluorobenzene (DNFB) at pH 8 to form yellow colored reaction products peaking at 383 nm and 390 nm for carvedilol and nebivolol, respectively. The absorbance-concentration plots were rectilinear over the concentration ranges of 5-30 and 4-28 µg/ mLwith the lower detection limits of 0.48 and 0.51 µg/mL and the lower quantitation limits of 1.45 and 1.54 µg/mL for cavredilol and nebivolol respectively. The different experimental parameters affecting the development and stability of the formed complex and reaction products were carefully studied and optimized for both methods. Both methods were successfully applied for determination of the studied drugs in their dosage forms.